Managing Traumatic Cataract in the Left Eye Following Blunt Trauma - Imelda, Eva; Emka, Erifa Ananda (Grimsa Journal of Science Engineering and Technology, 2024)
Cataract is an opacity of the lens that causes a progressive decrease in visual acuity. Cataracts are the leading cause of blindness in the world and can be caused by many factors. This case report aims to identify and recognize the symptoms of cataract and appropriate management in a patient with traumatic cataract. A 54-year-old male patient came to the Eye Polyclinic of Dr. Zainoel Abidin Regional General Hospital Banda Aceh with complaints of blurred vision in the left eye like a fog that has been felt since 8 months ago after an accident and the left eye was hit by a motorcycle handlebar where the patient felt the complaint worsened in the past 2 months. Initially the patient felt glare when looking at light or car lights at night. On ophthalmologic status examination, it was found that the OS visus was 1/300 and the OS lens was cloudy. The patient was diagnosed with traumatic cataract OS ec blunt trauma. The management performed on the patient was lens extraction using the small incision cataract surgery (SICS) method and intraocular lens (IOL) insertion. The patient's vision improvement after cataract surgery was 5/24 at the first follow-up, 5/18 at the second follow-up, 5/9 at the third follow-up and there were no other ocular abnormalities due to trauma.